ANALISIS PERAN BUMDES DALAM MENINGKATKAN PEREKONOMIAN MANDIRI DESA TAMBUSAI UTARA - Nurhayati (Jurnal Ilmiah Cano Ekonomos, 2023)
Development is a continuous process and covers all fields which are carried out thoroughly by all levels of society of the Unitary State of the Republic of Indonesia (NKRI). Village development is basically the basis of national development, because if each village is able to carry out development independently, the prosperity of the community will easily be realized and nationally it will increase the prosperity index of the Indonesian people. One of the forms of achieving economic growth and development in rural areas that the government is currently intensively carrying out is through socialization development activities for Village Owned Enterprises (BUMDes). BUMDesa Rantau Kasai has the main business of savings and loans and an LPG gas base. The purpose of this research is to find out the role of Rantau Kasai BUMDes in improving the village's independent economy. Methods of data analysis using multiple linear regression, while testing the hypothesis is done with the t-test using SPSS. The results showed that the data analysis using the multiple linear regression method was obtained for each variable, namely the value of benefits or social (X1), community participation (X2), innovation (X3) and business activity (X3). probability (sig t) is less than 0.05, so it can be concluded that all research variables have a positive and significant effect on economic development in North Tambusai Village.